RE-ENVISIONING EFL CLASSROOMS: SYNERGIZING TASK-BASED INSTRUCTION AND DIGITAL TECHNOLOGY (Ustozlar uchun, 2026)
In the contemporary era of global connectivity, English as a Foreign Language (EFL) education requires a departure from rigid, structural teaching paradigms. Traditional methodologies that overemphasize rote memorization of syntax frequently fail to cultivate functional fluency in real-world scenarios. This paper explores the pedagogical synthesis of Task-Based Language Teaching (TBLT) and modern digital software as a mechanism for authentic language acquisition. By organizing instruction around communicative goals rather than explicit grammar drills, TBLT encourages active intellectual engagement from learners. When this framework is enhanced by web-based collaborative platforms, multimedia tools, and interactive networks, it creates an immersive environment in which target-language use becomes essential for collaborative problem-solving. This study investigates the theoretical frameworks supporting digital TBLT, reviews current empirical evidence regarding its implementation, and offers practical classroom models. Ultimately, it demonstrates that technology-mediated tasks not only advance pragmatic capabilities but also foster vital 21st-century competencies, such as digital literacy and cross-cultural teamwork.